PENG ARUH ORIENTASI PROFESIONAL TERHADAP KONFLIK PERAN DENGAN TIPE PENGENDALIAN SEBAGAI VARIABEL MODERATING - Dwi Fitri Puspa (Media Riset Akuntansi, Auditing & Informasi, 2008)
The number of professionals working in bureaucratic organisational settings has been increasing. The organisations may use either formal administrative or bureaucratic controls (output and behaviour controls). As employees, these professionals often expect their behaViOlft to be controlled only through the use informal contols such as self and social control process The confluence of a high professional orientation and abureaucratrccontrol environmental will cause role conflict. This study examines the level of conflict incurred experienced when a formal administrative controls, such as accounting control, are implemented in organisations dominated by professionals It also examines the relationship between role conflict and sub-unit performance. Respondents participated in the study were academics working in private university Questionnaires were administered to 250 academics. To assess whether the interaction between a high professional orientation and the control environmentalaffects role conflict, a multiple regression analysis was used. The impact of role conflict on sub-unit performance was tested by examining the correlation coefficients. The results showed that academics working in private university did not experience role conflict. Therefore, role conflict did not correlate with subunit performance.Key Words: Role Conflict, Orientation Professional, Control, Job Satisfaction and Sub-unit Performance.